ALUR PENDAFTARAN, PENETAPAN DAN PEMBAYARAN PBB WAJIB PAJAK BARU DI BAPENDA JOMBANG - Moh. Fathulloh; Siti Ulfah Rochmawati; Rachma Agustina (LPPM UNIVERSITAS HASYIM ASY'ARI TEBUIRENG JOMBANG, 2022)
Abstract: One of the sources of tax funds comes from the Land and Building Tax. Land and Building Duty (PBB) is the middle recorded in the State Income and Consumption Spending plan (APBN). The motivation behind this examination is: